Conflict among athletes and their coaches: what is the theory and research so far? - Wachsmuth, S.; Jowett, S.; Harwood, C. G. (International Review of Sport and Exercise Psychology, 2017)
Although social and personal relationships are vital for productivity, health and wellbeing, conflict is inevitable and is likely to cause upset and hurt feelings as well as anxiety and distrust. Despite the potentially central role of interpersonal conflict in sport, researchers have yet to pay concerted attention to exploring the nature of conflict, its antecedents and consequences. Following a thorough literature search 80 research papers were identified, of which only a small number (6) studied interpersonal conflict directly, most captured dysfunctional interpersonal processes such as breakdown of communication. The current review aims to provide a critical summary of the existing literature around the psychological construct of interpersonal conflict, including its antecedents, management strategies and outcomes within the context of coach-athlete relationships as well as other relational contexts in sport. Based on the relevant literature, a framework of interpersonal conflict is proposed, which includes a specific focus on a key dyad within sport coaching - namely the coach-athlete dyad. Future research directions and potential practical implications for sport psychology consultants, coach educators, coaches and athletes as well as other stakeholders are discussed.